2010
DOI: 10.1051/0004-6361/200912473
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared flares of Sagittarius A*

Abstract: Context. We report on the results of new simulations of near-infrared (NIR) observations of the Sagittarius A* (Sgr A*) counterpart associated with the super-massive black hole at the Galactic Center. Aims. Our goal is to investigate and understand the physical processes behind the variability associated with the NIR flaring emission from Sgr A*. 2007 and 28 may 2008). We used a model of synchrotron emission from relativistic electrons in the inner parts of an accretion disk. The relativistic simulations have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 82 publications
7
109
0
Order By: Relevance
“…In the framework of the evolving spot model presented in Eckart et al (2008a) this may be explained by an evolution of the spot characteristics similar to the models presented by Hawley & Balbus (1991 and Yuan et al (2008). The recent theoretical approach of hot spot evolution due to shearing is highlighted in Eckart et al (2008a) and Zamaninasab et al (2008Zamaninasab et al ( , 2009; see also Pecháček et al 2008). Yuan et al (2008) explicitly solved the relativistic hydrodynamics and found initial expansion velocities of less than 0.01c close to the accretion disk followed by relativistic expansion towards the end of the flare.…”
Section: Modeling the April 4 2007 Nir/x-ray Light Curvesmentioning
confidence: 55%
See 1 more Smart Citation
“…In the framework of the evolving spot model presented in Eckart et al (2008a) this may be explained by an evolution of the spot characteristics similar to the models presented by Hawley & Balbus (1991 and Yuan et al (2008). The recent theoretical approach of hot spot evolution due to shearing is highlighted in Eckart et al (2008a) and Zamaninasab et al (2008Zamaninasab et al ( , 2009; see also Pecháček et al 2008). Yuan et al (2008) explicitly solved the relativistic hydrodynamics and found initial expansion velocities of less than 0.01c close to the accretion disk followed by relativistic expansion towards the end of the flare.…”
Section: Modeling the April 4 2007 Nir/x-ray Light Curvesmentioning
confidence: 55%
“…In a few years further polarimetric NIR observations at high angular resolution and sensitivity will help to distinguish between the importance of the different emission mechanisms in the low state of SgrA*. Interferometric observations in the nearinfrared using GRAVITY at the VLTI Straubmeier et al 2008;Zamaninasab et al 2009) and in the mm-wavelength domain (e.g. Fish et al 2009;Doeleman et al 2009) will be important to understand the emission from SgrA*.…”
Section: Discussionmentioning
confidence: 99%
“…Only rapid millimeter to X-ray variability (Baganoff et al 2001;Genzel et al 2003;Ghez et al 2004Mauerhan et al 2005Eckart et al 2004Eckart et al , 2006aEckart et al , 2008Yusef-Zadeh et al 2008) as well as significant polarization features in the near-infrared (Eckart et al 2006b;Zamaninasab et al 2010Zamaninasab et al , 2011 indicate the presence of matter on relativistic orbits close to SgrA*. However, the radius at which the electrons become relativistic and suppress Faraday rotation within a thermal electron gas is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (e.g. Schnittman et al 2006;Pecháček et al 2008;Eckart et al 2006b;Zamaninasab et al 2010) have shown that a multi-component hot spot scenario can reproduce the observed flare emission and the overall behavior of the observed SED.…”
Section: Introductionmentioning
confidence: 98%
“…The beam was subsequently restored with a Gaussian of a FWHM near the diffraction limit. These data reduction and deconvolution steps were also taken for polarimetric data (Zamaninasab et al 2010;Witzel et al 2011, in prep.). In these cases, flux densities of observations made with the Wollaston prism were obtained by summing the two orthogonal channels.…”
Section: Introductionmentioning
confidence: 99%